2016
DOI: 10.1080/09540121.2016.1147018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of pediatric disclosure among HIV-infected Nigerian children on treatment

Abstract: This cross-sectional, facility-based study aimed to determine the prevalence, age, and main agent of disclosure among Nigerian children on antiretroviral therapy. It also sought to elicit barriers to, and facilitators of disclosure; and any association between disclosure and health outcomes. A semi-structured questionnaire was administered to 110 parents/caregivers of children ≥6 years. CD4 count, viral load, opportunistic infections and adherence information were also extracted from medical records for all 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…For example, most children studied in the earlier report were pre-adolescent (mean age 8.8 ± 2.2 years) compared to our study in which the majority were in early and mid-adolescence (mean age 12.2 ± 3.2 years), making disclosure more likely in our study with corresponding higher prevalence. More recent studies in Nigeria by Ubesie et al, [20] and Odiachi et al [21] reported prevalence of disclosure to HIV positive children of 29.5 and 30.9% respectively; comparable to our findings which suggests an increase prevalence of disclosure to Nigerian children living with HIV within recent time. Although relatively higher than most reports from within Nigeria and the African continent, [5,[22][23][24][25][26][27][28] our disclosure rate are lower compared with findings from the US, Canada and Europe [29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…For example, most children studied in the earlier report were pre-adolescent (mean age 8.8 ± 2.2 years) compared to our study in which the majority were in early and mid-adolescence (mean age 12.2 ± 3.2 years), making disclosure more likely in our study with corresponding higher prevalence. More recent studies in Nigeria by Ubesie et al, [20] and Odiachi et al [21] reported prevalence of disclosure to HIV positive children of 29.5 and 30.9% respectively; comparable to our findings which suggests an increase prevalence of disclosure to Nigerian children living with HIV within recent time. Although relatively higher than most reports from within Nigeria and the African continent, [5,[22][23][24][25][26][27][28] our disclosure rate are lower compared with findings from the US, Canada and Europe [29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…Vaz et al ( 4 ) reported only 3% pediatric disclosure in their study in the Democratic Republic of Congo, while Vreeman et al ( 7 ) also reported almost 100% non-disclosure in Kenya. More recent studies in SSA have similarly reported low disclosure rates—13.5% ( 8 ) and 30.9% ( 9 ) in Nigeria; 21% ( 10 ) in Ghana; 17.4% ( 11 ) and 39.5% ( 12 ) in Ethiopia; 19% ( 13 ) and 26% ( 14 ) in Kenya; and 32.6% ( 15 ) in Cote d’Ivoire.…”
Section: Introductionmentioning
confidence: 87%
“…Factors that influence pediatric disclosure include child’s age and cognitive development ( 10 , 12 ); concerns around antiretroviral therapy (ART) adherence ( 8 , 9 ); imminent onset of sexual activity ( 4 ); and the need to protect others from infection ( 16 ). Benefits of pediatric disclosure include improved adherence to ART, and psychosocial well-being and mental health ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although both child and caregiver related factors have been identified as barriers in disclosure to perinatally infected children, often studies that investigate disclosure to children focus on child related factors with the exception of caregiver related factors: The most cited child related factors for nondisclosure include perceived young age of the child, child's perceived ability to understand the meaning of HIV, and concerns that disclosure would have negative consequences for the child. There are also numerous child related fears that are cited as barriers to disclosure such as the fear that the child would tell others about their HIV status, fear of stigmatization, social rejection, and isolation, fear of the children's resentment, and fear that disclosure would hurt the child [2, 4, 5, 79, 1315]. From the limited data on caregiver related barriers to disclosure, the most commonly cited include lack of HIV knowledge, lack of communication skills on HIV, lack of skills on how to conduct HIV disclosure, fear of answering questions related to the source of the HIV infection, unpreparedness for HIV related questions, lack of adequate knowledge about the benefits of disclosure, emotional unpreparedness to disclose, and fear of being judged and blamed by the adolescent [9, 10, 16, 17].…”
Section: Introductionmentioning
confidence: 99%